2020
DOI: 10.1002/anie.202007030
|View full text |Cite
|
Sign up to set email alerts
|

Grubbs Metathesis Enabled by a Light‐Driven gem‐Hydrogenation of Internal Alkynes

Abstract: [(NHC)(cymene)RuCl 2 ] (NHC = N-heterocyclic carbene) complexes instigate a light-driven gem-hydrogenation of internal alkynes with concomitant formation of discrete Grubbs-type ruthenium carbene species. This unorthodox reactivity mode is harnessed in the form of a "hydrogenative metathesis" reaction, which converts an enyne substrate into a cyclic alkene. The intervention of ruthenium carbenes formed in the actual gem-hydrogenation step was proven by the isolation and crystallographic characterization of a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 69 publications
1
29
0
Order By: Relevance
“…Even ruthenium as the central atom can be replaced, although the formation of the corresponding osmium complex 6 was much less efficient for reasons that are not entirely clear at this point [30] . Despite the poor productivity, this example is important from the conceptual viewpoint in that it shows for the first time that discrete carbene complexes involving metals other than ruthenium can be generated by gem hydrogenation [1–8] . In view of the importance of metal carbenes in general as catalysts or reactive intermediates, this finding is deemed to provide an encouraging outlook.…”
Section: Methodsmentioning
confidence: 84%
See 4 more Smart Citations
“…Even ruthenium as the central atom can be replaced, although the formation of the corresponding osmium complex 6 was much less efficient for reasons that are not entirely clear at this point [30] . Despite the poor productivity, this example is important from the conceptual viewpoint in that it shows for the first time that discrete carbene complexes involving metals other than ruthenium can be generated by gem hydrogenation [1–8] . In view of the importance of metal carbenes in general as catalysts or reactive intermediates, this finding is deemed to provide an encouraging outlook.…”
Section: Methodsmentioning
confidence: 84%
“…In a recent Communication, we reported that ruthenium complexes of the general type [(NHC)(η 6 ‐cymene)RuCl 2 ] ( 1 ) are able to effect the geminal hydrogenation of internal alkynes, provided that the reaction mixture is irradiated with UV‐A light ( λ =370±40 nm) [1] . Delivery of both H‐atoms of H 2 to the same C‐atom of the triple bond (“ gem hydrogenation”) entails concomitant formation of a discrete metal carbene at the adjacent position (Scheme 1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations